PENANAMAN NILAI KARAKTER PEDULI LINGKUNGAN DALAM PEMBELAJARAN PPKN MELALUI PROGRAM PENGELOLAAN SAMPAH ANORGANIK MENJADI KERAJINAN PADA PESERTA DIDIK KELAS VII SMP NEGERI 18 SURAKARTA - Nisa Mauliana Sari; Yusuf Yusuf; Sugiaryo Sugiaryo (Prodi PPkn Universitas Slamet Riyadi, 2023)
The aims of this study were 1) to find out about inculcating environmental care character values through inorganic waste management into crafts in the P5 program, 2) to find out the obstacles in inculcating environmental care character values through inorganic waste management into crafts in the P5 program, 3) to find out the solution to the obstacles in inculcating environmental care character values through inorganic waste management into crafts in the P5 program. This study used descriptive qualitative method. The research location was at SMPN 18 Surakarta. The research subjects were teachers, school principal, and students. The method of collecting data in this study was through interviews, documentation, and observation. To check the validity of the data in the research, source triangulation and technical triangulation techniques were used. The data analysis technique was to use descriptive qualitative with an interactive model starting from data collection, data reduction, data display, and drawing conclusions. The results showed that 1) teaching students about inculcating of value of environmental care character through the P5 program on managing inorganic waste into crafts, 2) obstacles in inculcating character through the waste management program into crafts occurred from within or from the conditions of the students and the limitations of tools and material. While external obstacles were from the family or environment. 3) the solution to these obstacles was to make rules and punishments, provide counseling to students' families and the environment to actively participate in environmental care activities. Keywords: Character Education, Environmental Care, Waste Management Programs into Crafts